Yield of active screening for tuberculosis among asylum seekers in Germany: a systematic review and meta-analysis - Bozorgmehr, Kayvan; Saure, Daniel; Szecsenyi, Joachim; Stock, Christian (Eurosurveillance, 2017)
All asylum seekers in Germany undergo upon-entry screening for tuberculosis TB, but comprehensive evidence on the yield is lacking. We compared the national estimates with the international literature in a systematic review and meta-analysis of studies reporting the yield of TB, defined as the fraction of active TB cases detected among asylum seekers screened in Germany upon entry. We searched 11 national and international databases for empirical studies and the internet for grey literature published in English or German without restrictions on publication time. Among 1,253 screened articles, we identified six articles reporting the yield of active TB based on German data, ranging from 0.72 (95% confidence interval (CI): 0.45-1.10) to 6.41 (95% CI: 4.19-9.37) per 1,000 asylum seekers. The pooled estimate across all studies was 3.47 (95% CI: 1.78-5.73; I2 = 94.9%; p < 0.0001) per 1,000 asylum seekers. This estimate was in line with international evidence (I2 = 0%; p for heterogeneity 0.55). The meta-analysis of available international estimates resulted in a pooled yield of 3.04 (95% CI: 2.24-3.96) per 1,000. This study provides an estimate across several German federal states for the yield of TB screening in asylum seekers. Further research is needed to develop more targeted screening programmes.